Robotic guide for the visually impaired through Bluetooth and obstacle avoidance using Arduino - Wong, Wina; Batumalay, Malathy; Muniandy, Balasubramaniam; Pagadala, Pavan Kumar; P, Vinoth Kumar (Review of Computer Engineering Research, 2025)
Visual impairment continues to affect a significant portion of the global population, with over 2.2 billion people experiencing some level of vision loss. Conventional aids such as white canes and guide dogs provide essential support but have notable limitations in certain environments. To address this gap, a robotic guide was developed using Arduino-based components, offering real-time obstacle detection through ultrasonic and infrared sensors. Audio feedback is transmitted via a Bluetooth-connected mobile application, and vibration alerts are included for individuals with hearing impairments. The system features a joystick for directional control and incorporates RFID-based security to prevent unauthorized access. Functionality tests with users indicate strong potential for improving navigational independence and safety in urban and controlled settings. The design emphasizes practicality, accessibility, and user adaptability for product innovation.